2019
DOI: 10.3390/electronics8070805
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in SNR by Adaptive Range Gates for RCS Measurements in the THz Region

Abstract: One of the major concerns in radar cross-section (RCS) measurements is the isolation of the target echo from unwanted spurious signals. Generally, the method of software range gate is applied to extract useful data. However, this method may not work to expectations, especially for targets with a large length-width ratio. This is because the effective target zone is dependent on the aspect angle. The implementation of conventional fixed range gates will introduce an uneven clutter signal that leads to a decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Equation ) can be written as Equation ) for RCS in dBsm units: σ=10log||Et2||E02+σ0 where, E t and E 0 are measured echoes of the target and reference target (sphere), respectively, and σ 0 is the theoretically calculated RCS (in dBsm units) of the reference target (sphere) 13 . The operation of Equations ) and ) takes care of all the magnitude conversions during various stages of signal conditioning and signal processing and proves to be a very useful tool in this case of somewhat nonconventional RCS measurement.…”
Section: Simulation and Measurement Resultsmentioning
confidence: 99%
“…Equation ) can be written as Equation ) for RCS in dBsm units: σ=10log||Et2||E02+σ0 where, E t and E 0 are measured echoes of the target and reference target (sphere), respectively, and σ 0 is the theoretically calculated RCS (in dBsm units) of the reference target (sphere) 13 . The operation of Equations ) and ) takes care of all the magnitude conversions during various stages of signal conditioning and signal processing and proves to be a very useful tool in this case of somewhat nonconventional RCS measurement.…”
Section: Simulation and Measurement Resultsmentioning
confidence: 99%
“…According to research, false target signals only remain for a short time when detected and can be eliminated by the Kalman filter [143], multiple-hypothesis target [144], and iterative adaptive approach [145]. In addition, some scholars have found that the radar cross-section (RCS) and signal-to-noise ratio (SNR) of stationary vehicles are much smaller than those of moving vehicles [146]. RCS refers to the extent to which an object is detected by radar, while SNR is the ratio of the desired signal power to the noise power.…”
Section: Target-level Radarmentioning
confidence: 99%
“…The experimental results are supported by numerical simulations demonstrating the validity of the proposed models. The improvement of radar cross-section using THz signals is shown and demonstrated in Reference [9], where the concept of adaptive gates is adopted to reduce the signal-to-noise ratio, thereby improving the accuracy of the measurement. The design of a frequency multiplier source working at 0.335 THz is reported in Reference [10] with two different schemes; experimental validations of the proposed designs are provided.…”
Section: In This Special Issuementioning
confidence: 99%